Screened realities: a Grounded Theory exploration of gaming disorder dynamics among Iranian male adolescents - Mazaherizadeh, Ali; Taherifar, Zahra; Farahani, Hojjatollah; Hussain, Zaheer (Frontiers in Psychiatry, 2024)
This qualitative study delves into the dynamics of Gaming Disorder (GD) and Internet Gaming Disorder (IGD) among Iranian male adolescents, utilizing Grounded Theory Methodology. The study includes a sample of 13 participants, who were assessed using the Gaming Disorder Scale for Adolescents and the Structured Clinical Interview for DSM-5. The research findings reveal that Iranian adolescents are drawn to gaming due to its potential for financial gain despite facing cultural and territorial obstacles. The study also uncovers a unique pattern of identity formation influenced by gaming, where adolescents shape their career aspirations and social identities around their online experiences. The research provides vital insights into the socio-cultural dynamics of GD in Iran, highlighting the significant impact of gaming on adolescents' life choices and identity development. The study is crucial since there is a shortage of qualitative research in this area, and it provides a psychological understanding of GD within the unique socio-cultural context of Iran.